2012
DOI: 10.1038/bjc.2012.354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic value of inflammation-based prognostic scores in patients with hepatocellular carcinoma

Abstract: Background:Inflammation-based prognostic scores including the Glasgow Prognostic Score (GPS), neutrophil to lymphocyte ratio (NLR), and Prognostic Nutritional Index (PNI) are associated with survival in patients with hepatocellular carcinoma (HCC). The aim of this study was to investigate the prognostic value of these inflammation-based prognostic scores in patients with HCC.Methods:In total, 150 patients with newly diagnosed HCC were prospectively evaluated. Patients were divided according to the GPS, modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
248
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(267 citation statements)
references
References 25 publications
17
248
1
1
Order By: Relevance
“…The NLR and PLR reflect the populations of circulating white cells and platelets and have clinical advantages of being inexpensive and routinely measured in perioperative practice. They are, inferior to some other markers of a cancer-related systemic inflammatory response, such as serum CRP and albumin, the Glasgow prognostic score (GPS) or modified GPS (mGPS) (28,29), but serum CRP levels and other markers are not routinely performed as part of the preoperative assessment of patients. Hence, the NLR and PLR plus the absolute neutrophil, lymphocyte and platelet counts were assessed in patients with thymic carcinoma who were retrospectively evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR and PLR reflect the populations of circulating white cells and platelets and have clinical advantages of being inexpensive and routinely measured in perioperative practice. They are, inferior to some other markers of a cancer-related systemic inflammatory response, such as serum CRP and albumin, the Glasgow prognostic score (GPS) or modified GPS (mGPS) (28,29), but serum CRP levels and other markers are not routinely performed as part of the preoperative assessment of patients. Hence, the NLR and PLR plus the absolute neutrophil, lymphocyte and platelet counts were assessed in patients with thymic carcinoma who were retrospectively evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The SII was defined as follows: SII = platelet count × neutrophil count/lymphocyte count (Hu et al 2014), and an SII ≥ 1,600 × 10 9 /L was considered as the cut-off value. The PNI was calculated as albumin + 5 × lymphocyte and PNI < 45 was considered as abnormal, as described previously (Kinoshita et al 2012).…”
Section: Patientsmentioning
confidence: 99%
“…Recently, several biomarkers and hematological indices representative of systemic inflammatory responses, including the neutrophillymphocyte ratio (NLR), the platelet-lymphocyte ratio (PLR), a combination of platelet count and neutrophil-lymphocyte ratio as systemic immune-inflammation index (SII), the C-reactive protein (CRP) and a combination of albumin and lymphocyte count as the prognostic nutritional index (PNI) that have been associated with poor prognosis in various cancers (Proctor et al 2011;Kinoshita et al 2012;Lee et al 2013;Hu et al 2014;Paramanathan et al 2014). Other hematological indices, including platelet count, hemoglobin (HGB), and the mean corpuscular volume (MCV) have been reported as potential predictors of survival, and have responded to chemotherapeutic agents in a limited number of studies (Dellapasqua et al 2012;Qu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Forrest et al reported that the Glasgow Prognostic Score (GPS), the combination of serum CRP and serum albumin, was a reliable, objective scoring tool for predicting survival rates in patients with inoperable non-small cell lung cancer (9). Additionally, several studies have demonstrated that GPS is associated with prognosis independent of age, stage and performance status in various types of malignancy (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%